Tribological behavior of plasma sprayed Al-Cu-Fe plus Sn quasicrystalline composite coatings - Shao, TM; Cao, XK; Fleury, E; Kim, DH; Hua, M; Se, D (ELSEVIER SCIENCE BV, 2004)
In this paper, we intend to present results on the effect of a soft phase,on the tribological properties of Al-Cu-Fe-based composite coatings. Quasicrystalline-based composite powders with a Sn volume fraction varying from 0% to 30% were prepared by gas atornization before deposition onto medium carbon steel substrates by the air plasma spray technique. The friction and wear behavior of the QC composite coatings was investigated in dry air with a ball-on-disk test machine under reciprocating motion. The results of this experimental investigation indicated that the addition of 20 vol.% Sn enabled an improvement of the wear owing to an enhancement of the fracture toughness of the composite coatings. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: HIGH-STRENGTH; ALLOYS